THE CONTRIBUTION OF NON TIMBER FOREST PRODUCTS TOWARD COMMUNITY REVENUE AROUND BUKIT RIMBANG BUKIT BALING WILDLIFE SANCTUARY - Kevin Natama Pardede; Evi Sribudiani; Defri Yoza (JURNAL ILMU-ILMU KEHUTANAN, 2018)
The forest-based activities in Indonesia that were judged to increase the income of the state, leading to massive decline of forest cover. Based on this, the government has established several conservation areas. One of the areas established by the government as a conservation area is the Bukit Rimbang Bukit Baling Wildlife Sanctuary. The communities surrounding the forest generally use existing forest products, especially Non Timber Forest Products (NTFPs), so it is important to know the amount of the contribution of NTFPs to the people's income. This research was conducted in Koto Lamo Village around of Bukit Rimbang Bukit Baling Wildlife Sanctuary area, Kampar Kiri Sub-district, Kampar District, Riau Province. The research that has been done shows the economic value of each NTFPs that is utilized, namely: jengkol is Rp 245.194.444, petai is Rp 179.648.780, durian is Rp 176.685.185, kulit resak is Rp 136.123.200, kembang semangkuk is Rp 121.309.756, duku is Rp 111.100.000, rotan manau is Rp 88.698.750, fruit rotan manau is Rp 79.195.000, langsat is Rp 62.515.384, idan is Rp 38.157.473, forest rambutan is Rp 35.828.000, tampui is Rp 31.119.121, mangosteen is Rp 17.054.074, biga bambu is Rp 14.280.000, rambai is Rp 13.368.750, kulit medang is Rp 10.971.428, honey is Rp 10.368.000, cempedak is Rp 9.173.333 and kabau is Rp 2.425 .833 and contributed to the income of the Koto Lamo Village community by 43.65%.